1999
DOI: 10.1126/science.284.5413.455
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the VHL-ElonginC-ElonginB Complex: Implications for VHL Tumor Suppressor Function

Abstract: Mutation of the VHL tumor suppressor is associated with the inherited von Hippel-Lindau (VHL) cancer syndrome and the majority of kidney cancers. VHL binds the ElonginC-ElonginB complex and regulates levels of hypoxia-inducible proteins. The structure of the ternary complex at 2.7 angstrom resolution shows two interfaces, one between VHL and ElonginC and another between ElonginC and ElonginB. Tumorigenic mutations frequently occur in a 35-residue domain of VHL responsible for ElonginC binding. A mutational pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
702
0
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 784 publications
(735 citation statements)
references
References 45 publications
23
702
0
10
Order By: Relevance
“…Modeling of C. elegans ELC‐1 and human TCEB1, a homolog of elongin C, was performed by using SWISS‐MODEL (http://swissmodel.expasy.org/) (Biasini et al ., 2014), based on the crystal structures of mammalian VHL–elongin C–elongin B complex and SOCS3–elongin B–elongin C complex (Stebbins et al ., 1999; Babon et al ., 2008). Structures were revisualized and aligned using PyMOL (http://www.pymol.org/) (Schrodinger, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Modeling of C. elegans ELC‐1 and human TCEB1, a homolog of elongin C, was performed by using SWISS‐MODEL (http://swissmodel.expasy.org/) (Biasini et al ., 2014), based on the crystal structures of mammalian VHL–elongin C–elongin B complex and SOCS3–elongin B–elongin C complex (Stebbins et al ., 1999; Babon et al ., 2008). Structures were revisualized and aligned using PyMOL (http://www.pymol.org/) (Schrodinger, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Structural analysis indicated that Cullin1 (most of the time abbreviated as CUL1) acts as a scaffold that directs other members of the SCF complex to bring the ubiquitin-loaded E2s and the substrate in proximity to promote the transferring of ubiquitin directly from the E2 to the substrates [26]. Besides Cullin1, recent data indicated that Cullin2 and Cullin3 also form similar groups of E3 ligases, in which an elongin C-SOCS module or a BTB protein replaces the SKP1-F-box protein module npg in the Cullin1-type SCF E3 ligase, respectively [27][28][29]. In the Arabidopsis genome, around 700 genes are predicted to encode proteins containing the 40 amino-acid F-box motif [30].…”
Section: Diversity Of Plant E3 Ligasesmentioning
confidence: 99%
“…The candidate 178-amino acid d-VHL protein can be aligned along its entire length with the smaller of the two h-VHLs ( Figure 1a; Gnarra et al, 1994;Beroud et al, 1998;Stebbins et al, 1999). d-VHL has an overall 22% identity to h-VHL and is 50% similar when conserved amino acid changes were considered ( Figure 1b).…”
Section: Cloning Of the D-vhl Gene Sequencementioning
confidence: 99%
“…One outstanding distinction between the two proteins, however, is that d-VHL lacks the N-terminal extension found in the larger form of the h-VHL. h-VHL gene encodes two biologically active proteins as a result of in-frame alternative AUG codon usage (Gnarra et al, 1994;Beroud et al, 1998;Stebbins et al, 1999). However, no functional signi®cance has been assigned to the extra 53 amino acids at the N-terminus of the large h-VHL.…”
Section: D-vhl Gain-of-function Phenotypesmentioning
confidence: 99%